Specific labeling and permanent activation of the retinal rod cGMP-activated channel by the photoaffinity analog 8-p-azidophenacylthio-cGMP. - Brown, R L (1993)
Cyclic nucleotide-gated ion channels play a key role in visual excitation and a variety of other signaling pathways. The photoaffinity probe 8-p-azidophenacylthio-cGMP (APT-cGMP) has been developed for structural and functional studies of the cGMP-activated channel of retinal rod outer segments. Using this analog, we have demonstrated both specific labeling of the channel in a partially purified biochemical preparation from bovine rod outer segments and permanent activation of the channel current in excised membrane patches from salamander outer segments. After UV illumination, a 32P-labeled version of APT-cGMP was shown by SDS/PAGE and autoradiography to be covalently attached to the 63-kDa channel subunit. This incorporation was significantly reduced by 8-Br-cGMP but was not reduced by 5'-GMP. In patch-clamp experiments APT-cGMP was a potent activator of the channel; APT-cGMP typically opened half of the channels in a patch at a 10-fold lower concentration than cGMP. Exposure of membrane patches to UV light in the presence of APT-cGMP resulted in a persistent current observed in the absence of bath-applied nucleotide. This current increased with repeated exposure of the patch to both UV light and fresh APT-cGMP, approaching the maximum current originally evoked by saturating (500 microM) cGMP. At this point, addition of 500 microM cGMP caused a negligible increase in current. The persistent current had several other properties expected of current through cGMP-activated channels: it was outwardly rectifying; outward current was blocked > 90% by 2 mM internal Mg2+, whereas inward current was blocked much less efficiently; a low concentration of cGMP caused a larger increase in current atop a half-maximal persistent current than it did originally. We conclude that the persistent current was caused by the covalent tethering of cGMP moieties to channel binding sites, resulting in irreversible channel activation. APT-cGMP should prove useful for further studies of these and similar cGMP-binding sites and in the identification of unknown cGMP-binding proteins.